Faktor-Faktor yang Berhubungan dengan Kejadian Anemia dalam Kehamilan - Putri Oktaviana; Triatmi Andri Yanuarini; Siti Asiyah (Jurnal Ilmu Kebidanan, 2022)
Anemia in pregnancy is one of the national problems because it reflects the value of the socio-economic welfare of the community and has a very large influence on the quality of human resources. This study aims to identify the factors associated with the incidence of anemia in pregnancy. The research method is literature review, journal search through Google Scholar and PubMed databases using keywords. There are ten selected journals that discuss the factors associated with the incidence of anemia in pregnancy. The results of a journal review stated that the factors associated with the incidence of anemia in pregnancy in developing countries consisted of 8 factors including maternal parity 5, low level of knowledge about anemia, pregnancy interval 2 years, residence in rural areas, third trimester gestational age, visits Irregular ANC, low nutritional status (LiLA 23.5 cm) and low economic status. While in Indonesia itself, the factors are the same as in other developing countries, only differing in the factors of how to consume Fe tablets which are not appropriate and the level of education is low and there are no sociodemographic factors and economic status. The level of knowledge is the most related factor with the incidence of anemia in pregnancy. So the factors related to the incidence of anemia in pregnancy are parity, knowledge, gestational distance, ANC visits, nutritional status, sociodemography, gestational age, economic status, adherence to Fe tablet consumption and education level.